Peningkatan Peningkatan Pengetahuan Wali Murid KB-TPA Aisyiyah Tentang DAGUSIBU (DApatkan, GUnakan, SImpan, dan Buang) Obat dengan Benar - Kurnia Oktaviani, Riska (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2024)
When managing medicines at home, there are still many people who do not understand how to store and dispose of medicines. People store syrup medicine in the refrigerator in the hope that the medicine will last even though this storage is not appropriate. This ultimately also causes harm to humans themselves. One way to manage drugs well and correctly is DAGUSIBU. This method explains the procedures for managing medicines from the moment they receive them until the time they are no longer consumed and are finally thrown away. Pharmacists as a health profession who are concerned about the use of medicines in society are encouraged to continue to provide DAGUSIBU education wherever they are so that people understand the correct use of medicines so that treatment goals can be achieved and do not cause environmental damage due to incorrect disposal of medicine waste. The results of the implementation of activities to increase the knowledge of the parents of KB-TPA Aisyiyah Gumawang students about DAGUSIBU on the correct use of medication showed that the parents of KB-TPA Aisyiyah Gumawang students felt happy and satisfied with the activities provided